Why do we get sick and old? From the perspective of the Darwinian medicine - Tadinac, Meri (2011)
From an evolutionary standpoint, it is reasonable to ask why we are plagued with disease, both physical and mental, and why we age. Evolution by natural selection has shaped, during millions of years, exquisite and sophisticated bodily mechanisms, so why has it not eliminated the causes of their illness and deterioration? Every day medical science gives us new facts about specific diseases, but we still understand little about why diseases exist at all. Why has the process of natural selection not eliminated the genes that make us susceptible to disease? Why has it not selected for genes that could enhance our ability to resist damage and enable bodily repairs to eliminate aging? It seems that some of our behaviours have also evolved contrary to what is good for us: we know that sun exposure causes skin cancer, but we still crave sunshine. Darwinian medicine tries to resolve some of these paradoxes, using evolutionary explanations. When analyzing a structure, a physiological process or behaviour, we can obtain two classes of explanations. Proximate explanations answer “what” and “how” questions, e.g. what each organ normally does and how a disease disrupts its function – the topics of most medical research. Ultimate explanations answer “why” questions about origins and functions. Darwinian medicine explores the ultimate causation, e.g. why is the body designed to be vulnerable to certain disorders or how the operation of adaptations that may once have served a useful purpose results in maladaptive or pathological consequences in modern environments. Seeing disease from the viewpoint of evolution helps us to understand disease and the mechanisms involved, which in turn can help us to fight disease. For example, some of the body's responses can be viewed as adaptive defenses (e.g. fever, morning sickness), others as the products of novel environments (e.g. fatty diet) or design compromises (e.g. walking upright predisposes man to back problems). The second major interest of Darwinian medicine is the problem of senescence - a process of bodily deterioration occurring at older ages. Some research indicates that the maintenance of the organism after the age of reproduction is not favoured by natural selection, and that sexual reproduction selects for mechanisms that increase the fitness in youth, at the cost for the organism in older age. We will present some of the key points of the relatively new field of evolutionary medicine and its implications for the way we view, understand, and treat disease.
Projekt MZOS
ENG